Prevalence of Acute Kidney Injury (AKI) in Females with Pre-Eclampsia in Tertiary Care Hospital - Kashaf, Memoona; Shah, Nighat Ali; Shahid, Aisha; Nasir, Fatima; Sheerin; Kiran, Aisha (Indus Journal of Bioscience Research, 2025)
Objective: To determine the prevalence of acute kidney injury (AKI) in females with pre-eclampsia in a tertiary care hospital setting. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, over a period of Three months from 20th March, 2025 to 20th June, 2025. Methodology: A total of 78 females aged 18–45 years with singleton pregnancies and a clinical diagnosis of pre-eclampsia after 20 weeks of gestation were enrolled using non-probability consecutive sampling. Patients with a prior history of renal disease, multiple gestations, fetal anomalies, or nephrotoxic drug use were excluded. Serum creatinine was measured, and the diagnosis and staging of AKI were done according to the RIFLE criteria. Data were analyzed using SPSS version 20. Chi-square test was applied to evaluate associations, with a p-value ≤ 0.05 considered statistically significant. Results: The mean age of participants was 29.8 ± 5.6 years, and the mean gestational age was 33.2 ± 3.4 weeks. Among 78 women, 19 (24.4%) were diagnosed with AKI. Of these, 9 (47.4%) had Stage 1, 6 (31.6%) had Stage 2, and 4 (21.0%) had Stage 3 AKI. AKI was significantly more prevalent among patients with severe pre-eclampsia (p = 0.02). Additionally, a higher frequency of AKI was observed in women with a history of diabetes and chronic hypertension. Conclusion: A substantial proportion of females with pre-eclampsia developed AKI, particularly those with severe disease and comorbidities such as diabetes and hypertension. Routine renal function assessment should be incorporated into antenatal care protocols for early detection and prevention of complications related to AKI.